2010
DOI: 10.1111/j.1600-6143.2010.03095.x
|View full text |Cite
|
Sign up to set email alerts
|

Histidine‐Tryptophan‐Ketoglutarate for Pancreas Allograft Preservation: The Indiana University Experience

Abstract: Histidine-tryptophan-ketoglutarate solution (HTK) has been scrutinized for use in pancreas transplantation.A recent case series and a United Network for Organ Sharing data base review have suggested an increased incidence of allograft pancreatitis and graft loss with HTK compared to the University of Wisconsin solution (UW). Conversely, a recent randomized, controlled study failed to show any significant difference between HTK and UW for pancreas allograft preservation. This study was a retrospective review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 28 publications
1
40
1
1
Order By: Relevance
“…The reasons for replacement of UWS by HTK can be partially related to economic considerations [25]. In agreement with numerous studies evaluating the effect of HTK on pancreas [2,4,6,7,26], kidney [27], and liver transplantation [3], the only islet studies that have been performed so far did not find any significant difference between HTK and UWS with regard to isolation and post-transplant outcome [12,13,28]. In contrast, several multicenter studies provided opposite results for pancreas [8], kidney [10,24], and liver transplantation [11].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The reasons for replacement of UWS by HTK can be partially related to economic considerations [25]. In agreement with numerous studies evaluating the effect of HTK on pancreas [2,4,6,7,26], kidney [27], and liver transplantation [3], the only islet studies that have been performed so far did not find any significant difference between HTK and UWS with regard to isolation and post-transplant outcome [12,13,28]. In contrast, several multicenter studies provided opposite results for pancreas [8], kidney [10,24], and liver transplantation [11].…”
Section: Discussionsupporting
confidence: 67%
“…Due to the low viscosity of HTK, some authors observed an enhanced clearance of the perfused organs compared with UWS, particularly when small vessels were used for flushing [4]. In this context, it has been speculated whether the adverse effect of HTK on graft survival is related to pancreas edema caused by using high perfusion volumes as recommended by the producer [4,7,26]. Although we did not observe obvious edema during gross inspection of the organ, the dry-to-wet weight ratio clearly indicated that the significantly higher weight of HTK-perfused pancreata was caused by a higher fluid content in the tissue.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The distal stumps of the SMA and SMV on the pancreas allograft side should be carefully controlled and oversewn or tagged with a fine nylon suture. Most simultaneous intestine and pancreas procurements performed for the institutional analysis study group used histidine-trytophan-ketoglutarate as the preservation solution for both in situ flush and storage as described elsewhere (8,9).…”
Section: Methodsmentioning
confidence: 99%
“…Using clearance of the portal venous effluent to determine volume of flush ex vivo is not advisable for the pancreas because it is difficult to exsanguinate the spleen. In the last decade, it is become increasingly apparent that minimizing cold ischemia (<12 h) is one of the single most important predictors of success in pancreas transplantation irrespective of donor quality or method of preservation (36)(37)(38)(39)(40).…”
Section: Principles Of Preservationmentioning
confidence: 99%